Doublement minoritaire : le cas de Matthew Mead, « independent minister » (c. 1630-1699) - Arlette Sancery (Revue Française de Civilisation Britannique)
At a time in England when religion cannot be dissociated from politics, Independent minister Matthew Mead (c.1630-1699) is nowadays almost forgotten, contrary to Baxter, another great voice among dissenters. Yet, he knew that all dissenters had to unite if they wanted to influence the leading politico-religious streams after the eviction of the Stuart monarchy following the Glorious Revolution. Hence his efforts, mostly through his preaching, to persuade both Congregationalists and Presbyterians to join “the happy union”. His failure does not put an end to his renown, as shown by the crowds who met at his funeral service.